Primary Cutaneous Aspergillosis - Nakashima, Keiko; Yamada, Nanako; Yoshida, Yuichi; Yamamoto, Osamu (Acta Dermato-Venereologica, 2010)
The overall agreement between different criteria for cervicitis in women infected with Chlamydia trachomatis and/or Mycoplasma genitalium, and in women who tested negative was examined. Women attending a clinic for sexually transmitted diseases were enrolled because of sexual partner’ suspected chlamydia infection. M. genitalium was tested in a sample of first-catch urine and an endocervical specimen, whereas specimens from four different sites were used for detection of C. trachomatis. Signs of friability and purulent endocervical discharge were documented at gynaecological examination. Specimens for microscopy were taken from the endocervix and urethra as well as the vaginal discharge, and bacterial vaginosis was examined for. The criteria being evaluated included cervical friability and/or pus; polymorphonuclear leukocytes (PMNL)/epithelium cell ratio in the vaginal discharge; and more than 30 PMNL per high-power field in the endocervical smear. The overall agreement of the indicators of cervicitis in women infected with C. trachomatis and/or M. genitalium was 40.5% (15/37), and for those women with negative tests 35.3% (12/34). The criteria for cervicitis require further evaluation, including study of a control group of women at low risk of having a sexually transmitted infection.